Reflections on Using Metaphors in Exploring Spiritual and Religious Needs with Young People with Cancer and their Families. Issue 2 (November 2015) - Nash, Paul; Nash, Sally
Abstract : Knowing what to say to a young person with cancer is often very difficult and even professionals in the field can lack confidence in engaging with the spiritual and religious dimensions of this. This article draws on a small-scale phenomenological research project commissioned by the oncology department, and undertaken, at Birmingham Children's Hospital, UK, by the chaplaincy team. It was designed to identify the spiritual and religious needs of young people with cancer and to explore the implications for enhancing patient care. Nine young people with cancer and their families participated in semi-structured interviews about their spiritual and religious needs. Oncology staff participated in two focus groups. Out of the research and subsequent work the chaplaincy team identified a range of metaphors which help to facilitate conversations exploring spiritual and religious needs with paediatric oncology patients and their families. This aspect of enhancing patient care is developed in this article. While careful attention needs to be paid to the demographic, developmental and cultural specificities in any encounter, it is proposed that these metaphors may have transferability or adaptability into other contexts where young people have experienced trauma.